THE SCOPE OF DOMESTIC VIOLENCE IN UZBEKISTAN: A LEGAL AND JUDICIAL ANALYSIS - Tursunmurodov Komron (Western European Studies, 2025)
This article examines the legal definition and scope of domestic (family) violence under the legislation of the Republic of Uzbekistan. It identifies the specific categories of individuals who may be considered subjects of domestic violence and highlights the limitations imposed by current legal definitions. Drawing from judicial practice, the article analyzes a case in which a misclassification of domestic violence occurred, emphasizing the importance of correct legal interpretation in qualifying acts committed within a household. The paper concludes that domestic violence can only be committed by persons in clearly defined intimate or familial relationships, and that other household members, such as in-laws, do not fall within this category under existing law. The discussion contributes to a broader understanding of legal accountability and the protection mechanisms provided to victims within domestic settings.
Keywords: domestic violence; Uzbek criminal law; legal subject